Evaluation of Thermal Imaging System of the Scrotum in Patients with Varicocele - Masoomeh DADPAY; Hossein GHAYOUMI ZADEH; Mostafa DANAEIAN; Farshad NAMDARI; Bijan REZAKHANIHA (Tehran University of Medical Sciences, 2017)
Evaluation of Thermal Imaging System of the Scrotum in  Patients with Varicocele